Bøgeskovgård V: En nordsjællandsk forrådsplads fra tidlig Maglemosekultur - Colding-Fagerholt, Oliver; Casati, Claudio (Kuml, 2025)
Bøgeskovgård V A foraging site from the Early Maglemose culture in North Zealand, Denmark In 2021, the site of Bøgeskovgård V, located north of Helsinge in North Zealand, was excavated by Museum Nordsjælland. The site was uncovered beneath an erosion layer during the excavation of an area containing multiple cooking pits from the Bronze Age. The excavated Mesolithic area covered 92 m2, and comprised primarily a single sand layer containing most of the finds, apart from those found in two features interpreted as pits with hearths for roasting hazelnuts. Pit A2 was the larger of the two pits, with two hearths, and A3 the smaller, with only a single hearth. They were identified due to the red hue of an overlying sand layer, caused by multiple heating episodes in the hearths. A substantial quantity of charred hazelnut shells was recovered from the pits, providing material for 14C dating, as well as an opportunity to understand the activities undertaken in the pits. The presumed primary use of the hearths was that a fire was made and subsequently covered with sand on which hazelnuts were roasted without exposing them directly to fire, which would have charred them and rendered them inedible. Features directly associated with the roasting of hazelnuts are a rare occurrence. Of those known, Duvensee WP6 and Erichshagen-Wölpe in Germany provide the best comparisons. It is also from these sites, together with Culverwell in England, that we became aware of the tools associated with nut-cracking, and these could, in turn, be identified in the lithic material from Bøgeskovgård V. The archaeological finds from the site mostly comprise flint artefacts: A total of 8332 pieces of flint, including 1.17 kg of calcined flint. The artefacts included 220 microliths, 189 microburins, 1571 microblades, 451 blades, 71 cores and three core axes. Other finds were charcoal, charred hazelnut shells and very small fragments of calcined bone, as well as tools of rock and sandstone, such as stones used for nutcracking. The lithics indicated a coherent inventory, both technologically and typologically, without any disturbances. Microliths provided the basis for a typological dating, which corresponds to the technical classification of the cores and blades. This places Bøgeskovgård V in phases 1-2 of the Maglemose culture. This is further supported by 14C dates for hazelnut shells, which indicate some of the earliest observed hazel in Denmark. The presence of both hazel and roasting pits is important, as it gives a rare insight into the life of the Mesolithic people and aspects of their activities that are rarely preserved. It is also due to these that the site is interpreted as a foraging site, which has been visited multiple times within the period.